Downregulation of aquaporins and PI3K/AKT and upregulation of PTEN expression induced by the flavone scutellarein in human colon cancer cell lines - Noor Tarawneh; Lama Hamadneh; Walhan Alshaer; Abdel Qader Al Bawab; Yasser Bustanji; Shtaywy Abdalla (Heliyon)
Scutellarein has an anticancer potential, but the pathway of its action has not been elucidated. This study investigated scutellarein efficacy against human colorectal cancer (CRC) and explored the possible pathway of its action. MTT assay was employed to detect scutellarein effect on HT-29, SW-480, and HCT116 cells viability. Scutellarein impact on programmed cell death was studied by Annexin V-FITC/PI and its role on migration and invasion was detected by wound healing and transwell chambers. Aquaporin (AQP) 1, 3, and 5 expression before and after scutellarein treatment was approached by quantitative polymerase chain reaction (RT‒qPCR) and immunostaining while Western blotting was used to explore scutellarein effect on PI3K/AKT pathway. Scutellarein induced apoptosis and necrosis in CRC cells, thus inhibiting proliferation, migration, and invasion. Colon cancer cells exhibited positive staining for AQP 1, 3, and 5 which was downregulated by scutellarein. PI3K/AKT pathway mediating cell proliferation and growth was also modulated by scutellarein; phosphatase and tensin (PTEN) was upregulated, whereas PI3K, AKT, and p-AKT expressions were downregulated, and the downstream mTOR and phosphorylated mTOR were also suppressed at the protein level. Data indicated that scutellarein suppressed growth, migration as well as invasion of these CRC cells by downregulating the expression of AQP 1, 3, and 5 and upregulating PTEN where the latter inhibited the genes and the proteins involved in PI3K/AKT pathway. The data indicate that scutellarein is a promising therapeutic agent that inhibits growth, migration, and invasion of CRC cells by down-regulating the expression of AQP 1, 3, and 5 and by PTEN up-regulation, thus inhibiting PI3K/AKT. These molecular alterations represent potential prognostic biomarkers for the metastasis of colon cancer, where the down-regulation of AQPs enhances patient survival.